PERAN ORANG TUA DALAM MENDUKUNG PERKEMBANGAN KOGNITIF ANAK USIA DINI - ROHMAH, SITI; Nurlaela, Euis; Iqbal Ramdhoni (Al Hanin, 2025)
Parental involvement in supporting the cognitive development of early childhood within the family environment remains relatively low. This study aims to identify the role of parents in providing cognitive stimulation and to describe effective forms of parental involvement in supporting children's intellectual development from an early age. The method used is a literature review, with data collected through a systematic search of books, scientific journals, and relevant research findings from the last five years. Data analysis techniques include data reduction, data presentation, and qualitative conclusion drawing. The findings indicate that active parental roles in interacting, guiding, and creating a supportive home environment significantly influence the optimization of children's cognitive functions. The conclusion of this study emphasizes that parental involvement in caregiving that incorporates cognitive stimulation—through educational play, communication, and the cultivation of critical thinking—serves as a key factor in shaping children's thinking abilities and lays the foundation for future academic success.